2007
DOI: 10.1111/j.1365-2761.2007.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of Photobacterium damselae ssp. piscicida phospholipase: an enzyme that shows haemolytic activity

Abstract: A phospholipase gene of Photobacterium damselae ssp. piscicida (ppp) was cloned from a genomic library and its nucleotide sequence was determined. The open reading frame consisted of 1218 bp encoding a protein of 405 amino acids with a predicted molecular mass of 46 kDa. The PPP had identities (53-55%) with phospholipase and haemolysin of Vibrio spp., while it showed low identities (23-26%) with glycerophospholipid cholesterol acyltransferase of Aeromonas spp. A recombinant PPP (rPPP) with a His tag at the C-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Two PL activities with different molecular masses were confi rmed in ECP of Phdp (Hu, 2005). The one with the lower mass was confi rmed as a phospholipase C (Hsu et al, unpublished results), while the one with the higher mass studied here was found similar to that reported by Naka et al (2007). These authors reported the hemolytic activity of a PL from the ECP of Phdp, but did not characterize this PL further.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Two PL activities with different molecular masses were confi rmed in ECP of Phdp (Hu, 2005). The one with the lower mass was confi rmed as a phospholipase C (Hsu et al, unpublished results), while the one with the higher mass studied here was found similar to that reported by Naka et al (2007). These authors reported the hemolytic activity of a PL from the ECP of Phdp, but did not characterize this PL further.…”
Section: Discussionsupporting
confidence: 79%
“…BAB85814). Therefore, the correspon ding gene sequence of the PL from Phdp (Naka et al, 2007) was cloned and expressed in Escherichia coli. The recombinant PL was purifi ed, characterized, and found to be a toxin of the bacterium in cobia (Rachycentron canadum).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of certain bacterial hemolysins is known to be enhanced after supplementation with exogenous lecithin (22,23). We found that the addition of lecithin to sheep erythrocytes caused a slight increase in the translucency of the hemolytic halo, whereas the presence of lecithin clearly enhanced the hemolysis of fish erythrocytes, not only in terms of halo translucency but also in terms of its diameter (Fig.…”
Section: Figmentioning
confidence: 64%
“…The haemolytic activity in Vibrionaceae can be related to extracellular enzymatic activities, such as phospholipases in V. parahaemolyticus, V. mimicus, V. harveyi and P. damselae subsp. piscicida (Shinoda et al, 1991;Lee et al, 2002;Zhong et al, 2006;Naka et al, 2007) and phospholipase D in P. damselae subsp. damselae (Kreger et al, 1987), or to the direct action of haemolysins that provoke the pore-structure formation on the erythrocyte membrane (Iida & Honda, 1997;Zhang & Austin, 2005).…”
Section: Pathogenicity and Virulence Factorsmentioning
confidence: 99%